Bilateral investment treaties and portfolio investment - Stefan Eichler; Jannik A. Nauerth (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2024)
We analyze the effect of bilateral investment treaties (BITs) on bilateral foreign portfolio investment in equity and debt securities. We find that expropriation risk and the level of a BIT's investor protection are complementary. Applying a Poisson Pseudo-Maximum-Likelihood model to a panel of 60 home and 39 host countries from 2002 to 2017, we find that host countries receive 40% more bilateral equity investment when they protect foreign investors with a BIT. This effect almost doubles when investment protection of BITs is strong, and the political risk of the host country is high.
urn:nbn:de:bsz:14-qucosa2-891689
Keywords: F32; G15; K33; 330; Bilateral investment treaties; Bilateral portfolio investment; Political risk; Investor protection; Emerging markets